Effect of disease acceptance in geriatric individuals on life satisfaction - Elif Ünsal Avdal; Selden Gül; Gökşen Polat; Gönül Düzgün (SERNEV, 2023)
Introduction: Elderly must maintain regular care and complex treatment of several chronic diseases that develop with age or that pre-exist. Having a chronic disease entail both a feeling of loss and the need to keep the disease and one's life under control. It is important for these individuals to accept their illness while maintaining treatment and care. Life satisfaction, on the other hand, is the result of comparing what a person has with his or her expectations. This analytical cross-sectional study was conducted to examine the effect of disease acceptance on the life satisfaction of geriatric individuals.Methods: The research type is analytical cross-sectional study. The research was conducted between February 1-July 31, 2019 in a hospital in Izmir, in Türkiye. A total of 140 individuals over the age of 65 were included. A sociodemographic questionnaire, the Disease Acceptance Scale, and the Life Satisfaction Scale were used as data collection tools.Results: The mean disease acceptance score of the elderly individuals was 25.95 ± 5.25, and the life satisfaction score was 20.39 ± 5.94. Cardiology, endocrinology, dermatology, and gastroenterology patients evaluated their health as good, while individuals with respiratory system diseases evaluated their health as bad. A significant relationship was also found between marital status, disease type, health assessment status, and life satisfaction. While the life satisfaction of married individuals was borderline significant, it was determined that the life satisfaction of individuals with respiratory problems and poor health status was low. When the scores of the two scales were compared, a moderate positive correlation was found.Conclusion: There is a strong correlation between the acceptance of illness and life satisfaction of elderly individuals. When older individuals accept their illness, their life satisfaction also increases. When older individuals accept their illness, their life satisfaction also increases. Socioeconomic status of elderly individuals and having more than one disease play an active role in accepting the disease and life satisfaction. The importance of accepting the disease should be considered in order to increase life satisfaction.Keywords: Aging, elderly, satisfaction